Understanding how to improve the use of clinical coordination mechanisms between levels of care. (20th October 2021) - Esteve-Matalí, L; Vargas, I; Plaja, P; Cots, F; Mayer, EF; Pérez-Castejón, JM; Escosa, A; Ramon, I; Abizanda, M; Vázquez, ML
Abstract: Background: Clinical coordination mechanisms (CCM) can play an important role in improving clinical coordination between primary (PC) and secondary care (SC) doctors, being necessary to understand the reasons hindering their use. The aim is to analyse the level of use of CCM, and the difficulties and factors associated to it. Methods: Cross-sectional study based on an online survey using the COORDENA-CAT questionnaire (October-December 2017). Sample: 3308 doctors of the Catalan national health system. Outcome variables: frequent use of six CCM and difficulties in their use. Explanatory variables: sociodemographic, labour characteristics, organizational and interactional factors. Stratification variable: level of care. Analysis: descriptive bivariate and multivariate by logistic regression. Results: The level of use differed according to the CCM and level of care, being lower for the different cross-level consultations (via electronic medical record -EMR: 52.36%, email: 26.11% and phone: 21.73%). Shared EMR of the organisation (81.27%) and of the region (65.89%), and joint clinical case conferences (63.28%) were the most frequently used, especially by PC doctors, and the ones presenting more difficulties in use. While the difficulties pointed to organizational problems, mostly related to computer and schedule problems, the analysis of factors pointed also to some individual factors. Working in integrated areas or with local hospitals were factors positively associated with the use of CCM. Interactional factors, such as personally knowing the other level doctor, were associated among SC doctors. Conclusions: The use of CCM differed across mechanisms and level of care, and was clearly improvable. Difficulties and factors affecting their use were mostly organizational, so managerial support is required to create the appropriate conditions for their use. It is also important to strengthen interaction between doctors of different care levels to improve the use of CCM. Key messages: The level of use of CCM differed according to the mechanism and level of care, and was clearly improvable. This study identifies difficulties and factors affecting their use, mainly organizational. These results are useful for managers promoting strategies to improve clinical coordination by the effective implementation of CCM, which require managerial support and interaction between doctors.